IMPACT PROFILE OF ENSO AND DIPOLE MODE ON RAINFALL AS ANTICIPATION OF HYDROMETEOROLOGICAL DISASTERS IN THE PROVINCE OF SOUTH SUMATRA - Melly Ariska; Hamdi Akhsan; Muhammad Muslim (Program Studi Fisika Universitas Negeri Jakarta, 2022)
El Niño Southern Oscillation (ENSO) is a weather phenomenon in the Pacific Ocean. At the same time, Dipole Mode (DM) is an ocean-atmosphere interaction phenomenon in the Indian Ocean. The area of South Sumatra Province, which is in the Monsunal area, makes the influence of ENSO and DM very instrumental in determining the length of the rainy season and throughout the year. The South Sumatra region is very vulnerable to forest and land fire disasters due to the condition of the area in the form of swamps and peatlands, which are very easy to burn if the dry season occurs in the South Sumatra area. In this study, an analysis of the effect of ENSO and DM on rainfall in the South Sumatra Region from 1981 to 2020 was carried out using a simple linear regression method and the correlation coefficient using Niño 3.4 index data and Dipole Mode with rainfall data and consecutive rainy days data. Consecutive Wet Day (CWD). The purpose of this study was to determine the effect of Enso and Dipole Mode on rainfall and CWD in the South Sumatra Region. The results show that the correlation between ENSO and rainfall is 0.0017-0.002573, DM and rainfall is 0.05972, and ENSO and CWD is -0.068. The correlation between DMI and CWD is 0.513. So it can be said that ENSO and DMI have no effect on rainfall in the South Sumatra Province. Still, the amount of CWD in South Sumatra Province is significantly determined by the Dipole Mode Index (DMI) at a moderate level. The number of consecutive rainy days in South Sumatra Province is influenced by the dynamics of the ocean and atmosphere of the Indian Ocean, which is characterized by the presence of positive IOD and negative IOD phenomena.